Ответ:
1)2а+5-7)(2а+5+7)=(2а-2)(2а+12)
2)(5х-2у)²-9у²=(5х-2у-3у)(5х-2у+3у)=(5х-5у)(5х+у)
3)p²-(3p+1)²=(p-3p-1)(p+3p+1)=(-2p-1)(4p+1)
4)(2a+b)²-(a-2b)²=(2a+b-a+2b)(2a+b+a-2b)=(a+3b)(3a-b)
5)(x+y)²-(x-y)²=(x+y-x+y)(x+y+x-y)=2y•2x=4xy
6)(4p-q)²-(2p+3q)²=(4p-q-2p-3q)(4p-q+2p+3q)=
(2p-4q)(6p+2q)
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
1)2а+5-7)(2а+5+7)=(2а-2)(2а+12)
2)(5х-2у)²-9у²=(5х-2у-3у)(5х-2у+3у)=(5х-5у)(5х+у)
3)p²-(3p+1)²=(p-3p-1)(p+3p+1)=(-2p-1)(4p+1)
4)(2a+b)²-(a-2b)²=(2a+b-a+2b)(2a+b+a-2b)=(a+3b)(3a-b)
5)(x+y)²-(x-y)²=(x+y-x+y)(x+y+x-y)=2y•2x=4xy
6)(4p-q)²-(2p+3q)²=(4p-q-2p-3q)(4p-q+2p+3q)=
(2p-4q)(6p+2q)